Deciphering the Role of Impurities in Methylammonium Iodide and Their Impact on the Performance of Perovskite Solar Cells. Issue 22 (19th September 2016) - Levchuk, Ievgen; Hou, Yi; Gruber, Marco; Brandl, Marco; Herre, Patrick; Tang, Xiaofeng; Hoegl, Florian; Batentschuk, Miroslaw; Osvet, Andres; Hock, Rainer; Peukert, Wolfgang; Tykwinski, Rik R.; et al.
Abstract : Solution‐based perovskite solar cell fabrication typically involves rather complex processing sequences to yield highest performance. While most studies concentrate on the exploration of processing conditions, the purity levels of common perovskite precursor solutions have been investigated and a number of impurities that are critically important toward controlling the crystallization of perovskites are found. In this study, an in‐depth chemical study of the possible impurities formed during CH3 NH3 I preparation is presented and their relevance on solar cell processing is revealed. A primary consideration is the chemical transformation of hypophosphorous acid, which plays the role of the stabilizer for HI. The detrimental role of the impurities is best demonstrated by comparing perovskite solar cell devices fabricated from impurity‐free precursors versus precursors containing different concentrations of impurities. Most interestingly, it is revealed that a certain concentration of impurities is detrimental to the growth of large‐grained crystals. PbHPO3 nanoparticles, which are formed after hypophosphorous acid transformation, actually cause crystal domain growth through serving as a nucleation center. This study gives valuable insight into the rate determining steps of perovskite crystal growth and further provides the basis for developing reliable and reproducible high‐performance recipes for perovskite solar cell processing. Abstract : A chemical study of the impurities formed during CH3 NH3 I preparation and their impact on solar cell processing is reported. These impurities initiate PbHPO3 nanoparticles formation in the perovskite precursor solution, with further seed growth of grains. The detrimental role of the impurities is best demonstrated by comparing perovskite solar cell devices fabricated from impurity‐free precursors versus precursors containing different concentrations of impurities.